16S rRNA TYPING OF CELLULOLYTIC BACTERIA FROM THE TERMITE ODONTOTERMES FORMOSANUS - D. Kavitha; K. Vijayarani; K.Kumanan (Indian Journal of Veterinary and Animal Sciences Research, 2024)
Odontotermes formosanus termites are recognized as one of the major ecosystem engineers in tropical soils. This termite depends on intestinal microorganisms for cellulose digestion. Nine bacterial isolates from termite gut were identified using sugar fermentation and biochemical tests and confirmed by 16S rRNA gene sequencing. The aerobes isolated from the termite gut were Bacillus sp., Citrobacter freundii and Pseudomonas aeruginosa. The facultative anaerobes isolated were Salmonella entrica, Enterococcus casseliflavus, Staphylococcus gallinarum and Serratia marcescens. DNA from these bacterial cultures was extracted for molecular identification by 16S rRNA gene amplification. The cellulolytic activities of these bacteria were assessed by congo red assay. This study revealed the presence of cellulolytic aerobic and facultative anaerobic bacteria in the gut of termite Odontotermes formosanus which could be manipulated for their cellulose digestion in rumen.